2017
DOI: 10.1016/j.molmet.2017.03.013
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin controls food intake and energy balance via NPY neurons

Abstract: ObjectivesInsulin signaling in the brain has been implicated in the control of satiety, glucose homeostasis and energy balance. However, insulin signaling is dispensable in energy homeostasis controlling AgRP or POMC neurons and it is unclear which other neurons regulate these effects. Here we describe an ancient insulin/NPY neuronal network that governs energy homeostasis across phyla.MethodsTo address the role of insulin action specifically in NPY neurons, we generated a variety of models by selectively remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 48 publications
7
109
1
6
Order By: Relevance
“…Glucose and insulin tolerance tests were performed on 6‐hour‐fasted or 4‐hour‐fasted mice that were administered intraperitoneally with glucose (1 mg/g body weight) or insulin (0.5 mU/g body weight), respectively. Blood glucose levels were assessed at 0, 15, 30, 60, and 90 minutes after glucose administration using an Accu‐Chek Go glucometer (Roche) as described …”
Section: Methodsmentioning
confidence: 99%
“…Glucose and insulin tolerance tests were performed on 6‐hour‐fasted or 4‐hour‐fasted mice that were administered intraperitoneally with glucose (1 mg/g body weight) or insulin (0.5 mU/g body weight), respectively. Blood glucose levels were assessed at 0, 15, 30, 60, and 90 minutes after glucose administration using an Accu‐Chek Go glucometer (Roche) as described …”
Section: Methodsmentioning
confidence: 99%
“…These diseases are caused by long-term energy metabolism disequilibrium, together with an imbalance between energy intake and energy expenditure. Studies have revealed that NPY is a major regulator in balancing energy metabolism [26, 94, 95] and resists excessive loss of fat by lipolysis in calorie-restricted mice indicating a trait potential for the life-extending effect of calorie restriction [95]. The NPY receptors, as is reported, can regulate energy balance and body weight in a cooperative manner.…”
Section: The Characteristics Of Human Npy Receptorsmentioning
confidence: 97%
“…Pre-diabetes is characterized by hyperinsulinemia, impaired glucose tolerance, as well as insulin resistance which is associated with the dysfunctional islet beta cells [108]. Previous studies demonstrated that in diabetes models, NPY exerts a profound role in the regulation of blood glucose homeostasis [26]. Insulin acts on NPY neurons and modulates the balance of energy regulation and the dysfunction of which may result in the development of metabolic diseases.…”
Section: The Characteristics Of Human Npy Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective inactivation of IR in these neurons showed that AgRP neurons, rather than POMC neurons are required for central insulin control of hepatic glucose production [18]. In the same manner, inactivation of IRs in NPY-expressing neurons induced an obese phenotype, leading to the conclusion that insulin signalling in NPY neurons controls food intake and energy expenditure [37]. Furthermore, insulin decreases expression of the orexigenic peptides AgRP and NPY, leading to decreased food intake and increased expression of POMC [38], resulting in increased levels of α-MSH, which promotes anorexia and increases energy expenditure [39].…”
Section: Central Insulin Signalling: Impact On Cognition and Metabolismmentioning
confidence: 99%